Cevimeline-induced anti-inflammatory effect through upregulations of mucins in the ocular surface of a dry eye mouse model - Kim, Chae Eun; Kim, Young Jin; Hwang, Moon Won; Park, Young Joon; Yang, Jaewook (Biomedicine and Pharmacotherapy, 2021)
This study aimed to investigate the effects of various concentrations of cevimelines (CVMs) and compare them with commercial drugs in a murine model of dry eye. The experimental mouse model used male and female NOD.B10.H2b mice over 12 weeks of age. Desiccation stress was performed at 30–40% ambient humidity, and subcutaneous injection of 0.5 mg/0.2 mL scopolamine hydrobromide was performed four times a day for 10 days. The efficacy of various concentrations of CVMs (seven experimental groups) was first evaluated, and then 2% CVM was compared with commercial drugs, such as cyclosporine A (CsA), diquafosol (DQS), and rebamipide (REB) (seven experimental groups). The clinical changes, including tear production, corneal irregularity, and fluorescein staining, were measured after the instillation of various concentrations of CVMs and commercial drugs for 0, 3, 5, 7, and 10 days. Histological changes, such as corneal detachment, conjunctival goblet cell and mucin density staining, were assessed by staining the cornea or conjunctiva with hematoxylin-eosin, periodic acid-Schiff, and alcian blue. The expression of inflammatory markers and mucin factors was detected by immunohistochemistry and immunofluorescence in the lacrimal gland, cornea, and conjunctiva. Tear production was significantly increased in the 2% CVM group and was similar to that in the DQS and REB groups (P < 0.05). The corneal smoothness and fluorescein staining score were significantly improved in the 2% CVM group and were similar to those in the REB group (P < 0.05). Corneal epithelial cells were significantly decreased in the 2% CVM group, with similar observations made in the DQS and REB groups (P < 0.05). The conjunctival goblet cells and mucin density recovered in the 2% CVM group were similar to those in the CsA and REB groups (P < 0.05). The 2% CVM group showed suppressed expression of inflammatory factors in the lacrimal gland and was comparable to that seen in the CsA and REB groups. The expression of mucin factors was upregulated in the cornea and conjunctiva of the 2% CVM group and was similar to that of the CsA and REB groups. In conclusion, administration of CVM resulted in recovery or clinical and histological improvement of the murine dry eye model, and all the observed parameters were comparable to those with commercial drugs.
Keywords: Animals; Anti-Inflammatory Agents, Non-Steroidal; Conjunctiva; Cornea; Dry Eye Syndromes; Epithelial Cells; Female; Lacrimal Apparatus; Male; Mice; Mice, Inbred NOD; Mucins; Ophthalmic Solutions; Quinuclidines; Tears; Thiophenes; Up-Regulation; Anti-inflammation; Cevimeline; Conjunctiva; Cornea; Dry eye; Mucin